OPTIMALISASI KECAKAPAN KADER POSYANDU DALAM PENINGKATAN KIA BERDASARKAN 25 KETERAMPILAN DASAR BATCH: PENGELOLAAN POSYANDU - Daniati, Dana (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2025)
Posyandu serves as a platform for community empowerment by disseminating information and skills from health workers (cadres) to the community and among community members, as well as bringing basic health services closer to the community. The objective of community service is to optimize the capabilities of Posyandu cadres in improving maternal and child health (MCH) based on 25 basic skills in Posyandu management. Community service applies the Participatory Action Research (PAR) method. The activity stages began with an analysis of maternal and child health issues, identification of solutions through cadre counseling, monitoring, and evaluation. The cadre training was held at the Kedungdung Community Health Center and involved 35 cadres. The level of understanding of basic Posyandu management competencies before the material was delivered showed that most cadres had sufficient knowledge, while after the material was delivered, most cadres demonstrated good knowledge. The community service activity was quite effective and successful in enhancing the skills of posyandu cadres in improving maternal and child health based on the 25 basic skills in posyandu management. For future activities, the program could be further optimized if more time is allocated and engaging audio-visual materials are used.